Oral hygiene practices among family of orthodontic patients- survey - PRIADARSINI T,; KUMAR, NAVEEN; GANAPATHY, DHANRAJ (The journal of contemporary issues in business and government, 2020)
Orthodontic care can lead to increased demineralisation , tooth decay and gingivitis. Poor oral hygiene is associated with greater incidence of white spot lesions. So, it is a challenging task to maintain acceptable oral hygiene to prevent dental caries and gingival inflammation . The aim of this study was to assess the oral hygiene practices among families of patients undergoing orthodontic treatment. A survey containing 14 questions were sent to patients undergoing orthodontic treatment through an online survey platform and the results were tabulated. The survey link was sent to patients who underwent orthodontic treatment. Around 60% of the respondents brush the teeth twice a day. 36% of them used extra soft toothbrushes than the hard bristled toothbrush , also 37% of the orthodontic patients and their families don’t use any other aids apart from brushing their teeth. From the results it was evident that the oral hygiene practises among orthodontic patients and their families was found to be good.